Germline Amino Acid Diversity in B Cell Receptors is a Good Predictor of Somatic Selection Pressures - Schwartz, Gregory W.; Hershberg, Uri (Frontiers in Immunology, 2013)
The diversity of the immune repertoire is important for the adaptive immune system's ability to detect pathogens. Much of this diversity is generated in two steps, first through the recombination of germline gene segments and second through hypermutation during an immune response. While both steps are to some extent based on the germline level repertoire of genes, the final structure and selection of specific receptors is at the somatic level. How germline diversity and selection relate to somatic diversity and selection has not been clear. To investigate how germline diversity relates to somatic diversity and selection, we considered the published repertoire of Ig heavy chain V genes taken from the blood of 12 individuals, post-vaccination against influenza, sequenced by 454 high-throughput sequencing. We here show that when we consider individual amino acid positions in the heavy chain V gene sequence, there exists a strong correlation between the diversity of the germline repertoire at a position and the number of B cell clones that change amino acid at that position. At the same time, we find that the diversity of amino acids used in the mutated positions is greater than in the germline, albeit still correlated to germline diversity. From these findings, we propose that while germline diversity and germline amino acid usage at a given position do not fully specify the amino acid mutant needed to promote survival of specific clones, germline diversity at a given position is a good indicator for the potential to survive after somatic mutation at that position. We would therefore suggest that germline diversity at each specific position is the better a priori model for the effects of somatic mutation and selection, than simply the division into complementarity determining and framework regions.